Optimizing the Village Lumbung in Jatisari Mijen Subdistrict Semarang as a Social Movement for Covid-Affected Communities 19 - RETNO, LAURA ANDRI (Seminar Nasional Pengabdian Kepada Masyarakat UNDIP 2020; Prosiding Seminar Nasional Pengabdian Masyarakat UNDIP 2020, 2020)
Without food, humans cannot continue their life. Lately, Indonesia is being attacked by the Covid-19 pandemic, which threatens food needs. There are various ways to overcome this threat, one of which is the Food Granary. Food Granary is a social mechanism formed by the village community in overcoming food shortages. This analysis aims to explain how to optimize the Village Granary in Jatisari Mijen Village, Semarang as a Social Movement for Communities Affected by Covid 19using case study. The results of this analysis will explainhow to optimize the Village Lumbung in the Mijen District community which has an impact on Covid-19.The object of this activity is located in KelurahanÂ  Jatisari Mijen Semarang.